Cross-cultural Theatre Education: Rehearsals and Performance. English as Lingua Franca, rewriting process, and poly-glottal text in psycho-physical acting practice - Henning, Lars (Nordic Theatre Studies, 2017)
At Copenhagen International School of Performing Arts, English is the Lingua Franca (ELF) of artistic exploration. With a non-conformist approach to the use of ELF, highlighting a body-mind insight into the language over correctness, a latent, expressive potential of ELF is explored through a psycho-physical training. The predominant technique is Movement Psychology (Laban/Malmgren), which examines the interdependence between, on the one hand, text, language, and narrative and, on the other, the embodiment of the Jungian unconscious. The paper analyses the process and the methods of staging the production entitled Re: ORESTES, based on Mee’s play Orestes 2.0, applying the described methodological exploration. The play was rewritten and remoulded by the performers throughout a rehearsal process, which focused on interlacing the performers’ highly diverse cultural horizons (Gadamer) in a common mega-text, in an attempt to fuse the familiar with the alien, the personal with the collective, and to channel, shape and articulate the material within ELF. The paper details two different examples of this transformative remoulding process. One actor wrote a completely new text, which was performed in the heightened style of "the Queen’s English". Another actor performed a part in a poly-glottal combination of Ancient and Modern Greek (her mother tongue) and ELF. In this process, both performers sought to transcend the preconceived limitations of their individual cultural horizons as well as of the English language.